Pengembangan Silabus dalam Pembelajaran - Wahyu Padila; Meyniar Albina (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This research aims to find out and understand the meaning of the syllabus, know and understand the benefits of the syllabus, know and understand the principles of syllabus development and so on. This research adapts the Research and Development (research and development) method. This method aims to produce certain products, and test the accuracy of these products (Sugiyono, 2013:407). The product in this research is a syllabus that was developed with reference to the structure and design of the 2013 curriculum. This shows that the resulting syllabus is suitable for use in preparing learning plans.